Dissociation of hydrogen peroxide in water and methanol through a biased molecular dynamics investigation. Issue 19 (11th May 2021) - Dong, Hieu C.; Ho, Thi H.; Nguyen, Thu M.; Kawazoe, Yoshiyuki; Le, Hung M.
Abstract: The two dissociation channels of HOOH, namely, HOOH and HOOH, in water and methanol are investigated using umbrella‐sampling ab initio molecular dynamics. Our potential of mean force calculations reveals the HOOH dissociation to be more favorable in methanol with a free energy barrier of 7.56 kcal/mol, while the HOOH dissociation possesses a free energy barrier of 11.46 kcal/mol. In water, the HOOH dissociation channel is more favorable (8.25 kcal/mol), while the HOOH dissociation process requires a higher free energy (11.28 kcal/mol). Such reaction favorability can be explained by inspecting the formation of secondary radical species during the course of multiple hydrogen donating‐accepting processes in each reaction channel. The radical species, that is, H3 O (observed in water) and CH3 OH2 (observed in methanol), are the first subordinate species upon the HOOH dissociation. For the HOOH dissociation channel in methanol, the secondary species such as water and formaldehyde can be observed, while the re‐generation of HOOH in water can be spotted. Abstract :